Are healthcare personnel at higher risk of seasonal influenza than other working adults?. (5th March 2020) - Coleman, Brenda L.; Kuster, Stefan P.; Katz, Kevin; Loeb, Mark; McNeil, Shelly A.; Muller, Matthew P.; Powis, Jeff; Simor, Andrew; Coleman, Kristy K. L.; Hatchette, Todd; McGeer, Allison; ,
Abstract: Background: Adults are at risk of being exposed to influenza from many sources. Healthcare personnel (HCP) have the additional risk of being exposed to ill patients. Objective: To determine whether HCP were at higher risk than adults working in nonhealthcare roles (non-HCP). Design: Prospective cohort study. Setting: Acute-care hospitals and other businesses in Toronto, Ontario, Canada. Methods: Adults aged 18–69 years were enrolled for 1 or more of the 2010/2011, 2011/2012, and 2012/2013 influenza seasons. Swabs collected during acute respiratory illnesses were tested for influenza and pre- and postseason blood samples were tested for influenza-specific immune response. Results: The adjusted odds of influenza were similar for HCP and non-HCP (odds ratio [OR], 1.29; 95% confidence interval [CI], 0.63–2.63). Older adults and those vaccinated against influenza had lower odds, and those who shared their workspace and who used corrective eyewear had higher odds of influenza. Conclusions: HCP and other working adults are at similar risk of influenza infection.